2018
DOI: 10.1111/1462-2920.14035
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐pumping rhodopsins are abundantly expressed by microbial eukaryotes in a high‐Arctic fjord

Abstract: Proton-pumping rhodopsins provide an alternative pathway to photosynthesis by which solar energy can enter the marine food web. Rhodopsin genes are widely found in marine bacteria, also in the Arctic, and were recently reported from several eukaryotic lineages. So far, little is known about rhodopsin expression in Arctic eukaryotes. In this study, we used metatranscriptomics and 18S rDNA tag sequencing to examine the mid-summer function and composition of marine protists (size 0.45-10 µm) in the high-Arctic Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…PR in dinoflagellates is highly similar to proteorhodopsin, which are globally abundant in bacteria (Béja et al 2013;Gómez-Consarnau et al 2010) and well characterized as a proton pump (Béja et al 2000;Inoue et al 2016). Since its first discovery in dinoflagellates (Lin et al 2010), eukaryotic homologs of PR have also been found in other eukaryotes microorganisms, such as diatoms, haptophytes and cryptophytes (Marchetti et al 2015), and recently found in arctic microbial eukaryotes (Vader et al 2018). The dinoflagellate homologs share the highly conserved residues with bacterial PR, including residues to bind retinal, absorbing light spectrum tuning, and proton donor and receptor residues (Lin et al 2010); this is true for the two homologs studied here, Pd-PR (Shi et al 2015), and Ac-PR (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…PR in dinoflagellates is highly similar to proteorhodopsin, which are globally abundant in bacteria (Béja et al 2013;Gómez-Consarnau et al 2010) and well characterized as a proton pump (Béja et al 2000;Inoue et al 2016). Since its first discovery in dinoflagellates (Lin et al 2010), eukaryotic homologs of PR have also been found in other eukaryotes microorganisms, such as diatoms, haptophytes and cryptophytes (Marchetti et al 2015), and recently found in arctic microbial eukaryotes (Vader et al 2018). The dinoflagellate homologs share the highly conserved residues with bacterial PR, including residues to bind retinal, absorbing light spectrum tuning, and proton donor and receptor residues (Lin et al 2010); this is true for the two homologs studied here, Pd-PR (Shi et al 2015), and Ac-PR (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…So far, only several studies have applied metagenomic shotgun sequencing to sea ice samples (e.g., Bowman et al 2014;Yergeau et al 2017), but the potential to elucidate complex polar microbial ecology questions is generally unrealized. Metagenomic sequencing efforts have demonstrated bacterial-mediated chemical cycling in frost flowers (Bowman et al 2014) and the importance of select photoreceptors in Antarctic and Arctic sea ice (Koh et al 2010;Vader et al 2018). With increasing throughput of sequence generation and decreasing costs, deep sequencing (i.e., sequencing the same locus multiple times) of the environment should allow comparative studies of full metagenomes to describe the metabolic potential (including uncultured strains) and strain level microbial diversity (e.g., Delmont et al 2017) in sea ice ecosystems.…”
Section: Advances In Microbial Ecologymentioning
confidence: 99%
“…While metagenomics can demonstrate the genetic potential of microbes, RNA-based studies, such as metatranscriptomics, can show whether the genes are expressed. For example, Koh et al (2010) and Vader et al (2018) showed that the genes for proteorhodopsin are actively transcribed in Antarctic and Arctic sea ice, indicating an active phototrophic bacterial community. Interdisciplinary research with biochemists identified the functions of translated proteins and ascribed a functional purpose for gene products used in survival and metabolism in sea ice (reviewed by Feller and Gerday 2003;Feng et al 2014).…”
Section: Advances In Microbial Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…With that, there is limited information on the expression of rhodopsins compared to other light-harvesting mechanisms. In contrast with the established global distribution and abundance of rhodopsin taxonomic clades, very few studies have compared their expression in environmental samples (Shi et al, 2011;Kopf et al, 2015;Boeuf et al, 2016;Brindefalk et al, 2016;Vader et al, 2018). Additionally, the vast majority of studies were based on single time-points, with the exception of Sabehi et al (2007), which compared winter and summer expression at two sites (Mediterranean and Sargasso Sea) and Nguyen et al (2015), which compared early-and late-winter expression in the arctic.…”
Section: Study Of Abundance and Expression Of Light-harvesting Mechanmentioning
confidence: 99%